The birth of indology as an Islamic science : Al-Biruni's treatise on yoga psychology - Kozah, Mario, 1976- (Islamic Philosophy, Theology and Science. Texts and Studies, 2015)
In The Birth of Indology as an Islamic Science Mario Kozah closely examines the pioneering contribution by Bīrūnī (d. circa 1048) to the study of comparative religion in his major work on India. Kozah concludes that a process of Islamisation is employed through a meticulous systematization of Hindu beliefs into one "Indian religion", preceding by almost a millennium the earliest definitions of Hinduism by nineteenth-century European Orientalists. This formulation of Hinduism draws on Bīrūnī's interpretation of Yoga psychology articulated in the Kitāb Bātanjal , his Arabic translation of the Yoga-Sūtra of Patañjali. Bīrūnī's Islamic reading of Hinduism relies on certain common denominators that he identifies as being of fundamental importance. In the case of Hinduism he identifies metempsychosis as its unifying banner.